2022
DOI: 10.7759/cureus.24468
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization of Blood Flow Velocity in the Anterior Humeral Circumflex Artery and Reduction in Night Pain After Arthroscopic Rotator Cuff Repair: A Case Report

Abstract: Rotator cuff tears are commonly associated with pain at rest and at night particularly if lying on the affected shoulder. This case describes a 54-year-old man who reported concerns of severe night pain in his left shoulder and had to undergo arthroscopic rotator cuff repair. The severity of night pain and blood flow velocity in the anterior humeral circumflex artery (AHCA) were measured over time. The patient reported his night pain as 10/10 on the numerical rating scale in the first week after surgery. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 20 publications
3
4
0
Order By: Relevance
“…Since redness observed on arthroscopy is often associated with pain symptoms, we hypothesized that this was the cause of the patient's pain. This finding has been confirmed by previous studies and our own experience [ 15 ].…”
Section: Discussionsupporting
confidence: 92%
“…Since redness observed on arthroscopy is often associated with pain symptoms, we hypothesized that this was the cause of the patient's pain. This finding has been confirmed by previous studies and our own experience [ 15 ].…”
Section: Discussionsupporting
confidence: 92%
“…This discrepancy may be due to differences in the measurement position, as Inoue et al [ 7 ] suggested that the SAS be measured during shoulder extension, resulting in microvessel loss due to compression. In our study, we examined the SAS with the shoulder joint at 30° of abduction [ 9 ], viewed over the coracoacromial ligament, to minimize compression. Conversely, the rotator interval in the previous study and where we measured GHJ reflect the same branches of the AHCA [ 16 ], resulting in consistent findings.…”
Section: Discussionmentioning
confidence: 99%
“…The bicipital groove and AHCA were identified by transverse scanning, then blood flow velocity in the AHCA was measured by longitudinal scanning, and the PSV was calculated by pulse Doppler ultrasonography ( Fig. 2 ) [ 9 ].…”
Section: Methodsmentioning
confidence: 99%
“… 29 Similarly, Watanabe et al revealed the association between PSV in the AHCA and night pain severity. 31 Furthermore, Asano et al revealed that PSV in the AHCA was associated with synovial inflammation severity. 1 The increased PSV in the AHCA may be attributed to inflammation based on the above.…”
Section: Discussionmentioning
confidence: 99%
“… 1 PSV of the AHCA is associated with the severity of synovitis in RCTs and is useful in assessing the inflammation of synovitis. 31 This could be due to an increase in blood flow velocity to supply blood to the abnormally increased neovascularization of the synovium. 8 Sachinis et al investigated blood biomarkers for the pathogenesis of pain in RCTs and revealed that inflammation and substance P, interleukin (IL)1a, IL1b, IL2, IL6, IL8, IL10, tumor necrosis factor -α, and vascular endothelial growth factor were related.…”
mentioning
confidence: 99%